Systematic review and meta‐analysis on non‐opioid analgesics in palliative medicine - Robert H. Schüchen; Martin Mücke; Milka Marinova; Dmitrij Kravchenko; Winfried Häuser; Lukas Radbruch; Rupert Conrad (Wiley, 2018)
Abstract Non‐opioid analgesics are widely used for pain relief in palliative medicine. However, there is a lack of evidence‐based recommendations addressing the efficacy, tolerability, and safety of non‐opioids in this field. A comprehensive systematic review and meta‐analysis on current evidence can provide a basis for sound recommendations in clinical practice. A database search for controlled trials on the use of non‐opioids in adult palliative patients was performed in Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, PsycINFO, and EMBASE from inception to 18 February 2018. Endpoints were pain intensity, opioid‐sparing effects, safety, and quality of life. Studies with similar patients, interventions, and outcomes were included in the meta‐analyses. Our systematic search was able to only identify studies dealing with cancer pain. Of 5991 retrieved studies, 43 could be included (n = 2925 patients). There was no convincing evidence for satisfactory pain relief by acetaminophen alone or in combination with strong opioids. We found substantial evidence of moderate quality for a satisfactory pain relief in cancer by non‐steroidal anti‐inflammatory drugs (NSAIDs), flupirtine, and dipyrone compared with placebo or other analgesics. There was no evidence for a superiority of one specific non‐opioid. There was moderate quality of evidence for a similar pain reduction by NSAIDs in the usual dosage range compared with up to 15 mg of morphine or opioids of equianalgesic potency. The combination of NSAID and step III opioids showed a beneficial effect, without a decreased tolerability. There is scarce evidence concerning the combination of NSAIDs with weak opioids. There are no randomized‐controlled studies on the use of non‐opioids in a wide range of end‐stage diseases except for cancer. Non‐steroidal anti‐inflammatory drugs, flupirtine, and dipyrone can be recommended for the treatment of cancer pain either alone or in combination with strong opioids. The use of acetaminophen in the palliative setting cannot be recommended. Studies are not available for long‐term use. There is a lack of evidence regarding pain treatment by non‐opioids in specific cancer entities.